2013
DOI: 10.11609/jott.o3423.5247-55
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural sampling techniques and activity pattern of Indian Pangolin Manis crassicaudata (Mammalia: Manidae) in captivity

Abstract: Funding: This study is a part of the research project funded by Central Zoo Authority, New Delhi.Competing Interest: Authors declare no competing interests.Author Details: R.K. Mohapatra is working as Junior Research Fellow; has registered for his PhD in Utkal University, Odisha with an objective to understand behavioural patterns, space utilization, reproductive biology, haematology, effect of environmental enrichment and identification of ecto-and endo-parasites of captive Indian pangolins which will be ulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The pangolin is a nocturnal animal that conceals its whereabouts, making it difficult to study. Recent research has addressed the behavioral patterns, time budget, and activity patterns of the Sunda pangolin (Challender, Thai, Jones, & May, 2012;Wang et al, 2015), Indian pangolins (Manis crassicaudata Gray, 1827; Mishra & Panda, 2010;Mohapatra & Panda, 2013, 2014a, 2014b, and Chinese pangolins (Manis pentadactyla Linnaeus, 1758; Chen, His, Chen, & Chang, 2005;Heath, 1987). However, little is known regarding their reproductive behavior.…”
mentioning
confidence: 99%
“…The pangolin is a nocturnal animal that conceals its whereabouts, making it difficult to study. Recent research has addressed the behavioral patterns, time budget, and activity patterns of the Sunda pangolin (Challender, Thai, Jones, & May, 2012;Wang et al, 2015), Indian pangolins (Manis crassicaudata Gray, 1827; Mishra & Panda, 2010;Mohapatra & Panda, 2013, 2014a, 2014b, and Chinese pangolins (Manis pentadactyla Linnaeus, 1758; Chen, His, Chen, & Chang, 2005;Heath, 1987). However, little is known regarding their reproductive behavior.…”
mentioning
confidence: 99%
“…Indian pangolins feed primarily on ants and termites. 1,7 The sloth bear has specialized on insect prey, particularly termites and ants. [8][9][10] About 72.7% of the sloth bear diet include termites.…”
Section: Discussionmentioning
confidence: 99%
“…Indian Pangolin (Manis crassicaudata) distributed throughout peninsular India, Sri Lanka, Bangladesh and Pakistan. 1,2 Knowledge on ecology and inter-specific association of Indian pangolin is limited because of their nocturnal and secretive habit. The Sloth bear (Melursus ursinus) is widely distributed on the Indian subcontinent-India, Nepal, Bhutan, and Sri Lanka and Bangladesh-ranges from the base of the Himalayas to the southern tip of the Western Ghats including the island of Sri Lanka.…”
Section: Introductionmentioning
confidence: 99%
“…Although several zoos have maintained this species, births in captivity have been reported by very few zoos: Calcutta zoo, (Acharjyo, 2000), Oklahoma zoo (Ogilvie & Bridgwater, 1967), Nandankanan Zoological Park, (Acharjyo & Misra, 1972, Acharjyo & Mohapatra, 1978. Although earlier studies have described nocturnal behaviour and activity pattern of Indian pangolins in captivity (Mishra & Panda, 2010;Mohapatra & Panda, 2013), observations on their mating behaviour are limited mainly because mating is seldom observed. This study reports on mating behaviour observed in captivity.…”
Section: On the Mating Behaviour Of Captive Indian Pangolin (Manis Crmentioning
confidence: 99%
“…The study was conducted at the "Pangolin Conservation Breeding Centre" (PCBC) of Nandankanan Zoological Park, Odisha, India. The housing and husbandry practices for Indian pangolins at PCBC have been described elsewhere (Mohapatra & Panda, 2013;Mohapatra & Panda, 2014). At PCBC, Indian pangolins are housed in such a way that they have the opportunity to interact with individuals of the opposite sex in the adjacent enclosure by climbing up mounds, the surrounds of water pools, wooden logs, or the chain-link mesh.…”
Section: On the Mating Behaviour Of Captive Indian Pangolin (Manis Crmentioning
confidence: 99%